Development of human mycoplasma vaccines: navigating the IL-17A paradox - Zhang, Wenjun; Li, Tingting; Guo, Fangyi (Frontiers in Immunology, 2025)
Despite decades of effort, effective vaccines against pathogenic human mycoplasmas remain elusive, largely due to vaccine-enhanced disease (VED). Recent discoveries highlight the paradoxical role of interleukin-17A (IL-17A) as both protector and instigator of pathology. Although IL-17A is indispensable for mucosal defense against many pathogens, its dysregulated expression following mycoplasma vaccination can provoke excessive neutrophilic inflammation and exacerbate pulmonary injury. This review synthesizes emerging evidence implicating bacterial lipoproteins as key triggers of maladaptive IL-17A responses. We delineate the duality of IL-17A in mycoplasma infections, mediating both protection and tissue damage, and critically examine its implications for vaccine design. Integrating insights from recent animal models, B-cell depletion studies, and proteomic analyses, we propose a framework for next-generation vaccines that elicit protective immunity while circumventing IL-17A-driven immunopathology.